Survey of ICT and Education in Africa : Nigeria Country Report - Tutu Agyeman, Osei (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. The Federal Republic of Nigeria has no specific policy for ICT in education. The Ministry of Education created its ICT department in February 2007, notwithstanding several government agencies and other stakeholders in the private sector having initiated ICT-driven projects and programs to impact all levels of the educational sector. The challenge is the lack of electric power and telecommunications infrastructure in a substantial part of the country. Mobile telecommunication currently covers 60 percent of the national territory, but mobile telephone companies generally power their base stations using electric power generators since the Power Holding Company of Nigeria (PHCN) is unable to supply them with power. This phenomenon is prevalent nationwide and constitutes the bottleneck to effective countrywide deployment of ICT in education. It is projected that Nigeria will be a net supplier of electric power by the end of 2007 when its massive cross-country electric power grid construction and interconnection projects are completed. It is hoped that mobile operators will introduce technologies that permit Internet access on their networks across the country to facilitate the implementation of e-learning programs.